Improvement of Laying Hen Performance by Dietary Prebiotic Chicory Oligofructose and Inulin - Chen, Y.C.; Nakthong, C.; Chen, T.C. (International Journal of Poultry Science, 2005)
Sixty White Leghorn hens (57 wk of age) were selected and divided randomly into three groups with two birds per cage. Twenty birds were assigned to each of the following diet treatments: 1) basal diet (control); 2) basal diet with 1.0% (w/w) of an oligofructose-type commercial prebiotic supplementation (Raftifeed®OPS); and 3) basal diet containing 1.0% (w/w) inulin, which was administered as 1.3% (w/w) of a semipurified chicory root extract (Raftifeed®IPE). The feeding trial lasted for 28 d. Oligofructose and inulin increased (P